Enzymatic profile in relation to physical parameters of Sabiwal bull semen - SWAIN, A K; SINGH, S V (The Indian Journal of Animal Sciences, 2014)
The semen samples were collected from 5 adult Sahiwal bulls at weekly intervals for 14 weeks continuously from February to May. The individual semen samples were evaluated for enzymatic activity and physical characteristics of semen. The mean enzymatic profiles of glutamic oxaloacetic transaminase (GOT) and glutamic pyruvate transaminase (GPT) were 730.71±5.04 and 45. 19± 1.05 units/ml of semen respectively. The alkaline and acid phosphatases mean activities were 690.89±13.99 and 538.42±9.62 KAu/ml respectively. The respective ratio of GOT:GPT and AKP:ACP were 16.72±0.35 and 1.29±0.02. Transaminases and phosphatases activities showed a significant (p